Corporate Governance, Corporate Social Responsibility and Firm Value: Evidence from Indonesia - Indri Kartika (International Journal of Business Economics (IJBE), 2021)
This study aims to determine the effect of good corporate governance on firm value and corporate social responsibility as a moderating variable. The sample of this research is manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the period 2012-2017. Based on purposive sampling criteria, there were 504 samples obtained This studi uses a quatitative approach with multiple linear regression analysis methods. This study found that good corporate governance has a positive effect on firm value. Then, corporate social responsibility strengthens the relationship between corporate governance and firm value. Contributions of this study is develops a research model of the influence of good corporate governance dan corporate social reponsibility on increasing firm value by measuring that variables in accordance with firm conditions in developing countries. Future resarch is very interesting to add criteria to determine the final score for good corporate governance and corporate social responsibility disclosure by following the changing times.